2017
DOI: 10.1163/1568539x-00003463
|View full text |Cite
|
Sign up to set email alerts
|

The role of abiotic and biotic cues in burrow habitat selection by juvenile crayfish

Abstract: Environmental cues contain critical information for individuals while searching for mates and suitable habitat. Crayfish have well-developed chemosensory abilities for detecting environmental cues in water; much less is known about these abilities on land. The Devil crayfish (Cambarus diogenes) is a burrowing crayfish often found in dense floodplain colonies as adults. Juveniles however are released in surface water and must navigate overland to burrow. Previous work demonstrates juveniles use cues from conspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…nov. are released and spend a period time in open water habitats before emerging to dig their first burrows in the banks or floodplain, which is a dispersal strategy that may contribute to the wide range of L. dalyae sp. nov. and other Lacunicambarus species (Helms et al, 2013;Clay et al, 2017;Glon et al, 2018). Based on their length-frequency histograms, Miller et al, 2014 suggested that the minimum lifespan of this species is 4 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…nov. are released and spend a period time in open water habitats before emerging to dig their first burrows in the banks or floodplain, which is a dispersal strategy that may contribute to the wide range of L. dalyae sp. nov. and other Lacunicambarus species (Helms et al, 2013;Clay et al, 2017;Glon et al, 2018). Based on their length-frequency histograms, Miller et al, 2014 suggested that the minimum lifespan of this species is 4 years.…”
Section: Resultsmentioning
confidence: 99%
“…Adults of burrowing crayfish species like L. dalyae sp. nov. often live in clustered colonies (Clay et al, 2017), but multiple burrowing crayfish species may also live in close proximity to one another in partially or completely overlapping colonies. For instance, we have collected C. gentryi Hobbs, 1970 andC.…”
Section: Updated Key To Lacunicambarusmentioning
confidence: 99%
“…Resultant of their reclusive lifestyle, our understanding of burrowing crayfish activity patterns and behavior is minimal, with much of the work on these species being derived from in situ natural history observations [12,[25][26][27][28][29] and not systematic investigations. However, despite these difficulties, semi-naturalistic mesocosms and custom-built observation chambers have been useful in the study of burrowing crayfish behavior [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%